International knowledge transfer in licensing agreements of educational products - Cioaca, Ionela (My University, 2019)
In the past years, there has been an increasing recognition that companies choose to enter different types of collaboration for acquiring new learning and efficiency through knowledge transfer. One of these collaborations is the international licensing agreement. However, in order to ensure successful international transfer of knowledge, it is necessary to understand how this process unfolds and what are the factors that enabled or hindered it. Therefore, the main objective of this research is to investigate how licensed partners deal with knowledge transfer in practice, by providing insights into the factors that affect the successful transfer of knowledge in the context of educational products. The study aims to reach its objective by analyzing the type of knowledge transferred through an educational product, the context-specific factors that influence the transfer and the role of licensed partners as facilitators of transfer. A qualitative research approach is used and semi-structured interviews with three representatives of the different licensed organizations are conducted. A multiple case study method has been selected and a cross-case analysis has been performed for analyzing the empirical results of the study. In the cross-case analysis was concluded that the international transfer of an educational product through licensing agreements is not just an exchange of information, but it involves a relationship where the role of the licensed partners should not be under-estimated. Empirical findings of the study have revealed that even if most of the knowledge received by licensed partners is explicit (with some exceptions) it should always be adapted according to the new context. Likewise, the most cited factors that affect the knowledge transfer process are the contextual and cultural ones such as: value conflicts, local community attitude or host country characteristics. Furthermore, a comprehensive approach to learning obtained through specific skills and capabilities of licensed partners is needed to ensure a successful transfer of knowledge. Thus, this study has several managerial implications, providing the developers of the program, the licensed partners or the future licensed partners with specific guidelines regarding on how to improve the international transfer of educational products.
Keywords: international knowledge transfer, licensing agreements, educational products